The perceived role of Islamic medical care practice in hospital: the medical doctor’s perspective - Rahman, Muhammad Khalilur; Zailani, Suhaiza; Musa, Ghazali (Emerald, 2018)
Purpose: This study aims to investigate the perceived role of the Islamic medical care practice of Muslim doctors in Malaysian Muslim-friendly private hospitals. Design/methodology/approach: Data were collection through self-administered questionnaires voluntarily submitted by the respondents. The survey covered selected major Muslim-friendly private hospitals in the country in the states of Kedah, Johor, Penang, Selangor, Kelantan and Kuala Lumpur. The non-probability purposive sampling was used, as the respondents and locations of the survey areas were predetermined. Findings: Five dimensions of the Muslim-friendly medical care practice were identified, namely, medical etiquettes, physical examination, proper cleansing process of blood and body fluids, proper handling and treatment of infectious diseases and doctors’ advice to Muslim patients. The findings also indicate that the scale development analysis produced excellent results which can be used for reproducible or repetitive medical care purposes and for integration facts and figures for inclusion into wider medical care policy and practices. Practical implications: The results from the study can further develop Islamic medical care practices and enable medical service providers to upgrade their performances to an enviable strategic status. Originality/value: Islamic medical care is a new mode of healthcare service market, as there are very few studies on this topic from the perspective of Muslim patients or no obvious facts are known. This study has first explored Muslim doctors’ perceived role in Islamic medical care practice in Malaysian Muslim-friendly private hospitals. This empirical study can immensely contribute to the further development of Islamic medical care practice for Muslim doctors in particular and for the Muslim-friendly hospital service marketing strategy in general.